2019
DOI: 10.1515/dx-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

A workshop to train medicine faculty to teach clinical reasoning

Abstract: Background Clinical reasoning (CR) is a core competency in medical education. Few studies have examined efforts to train faculty to teach CR and lead CR curricula in medical schools and residencies. In this report, we describe the development and preliminary evaluation of a faculty development workshop to teach CR grounded in CR theory. Methods Twenty-six medicine faculty (nine hospitalists and 17 subspecialists) participated in a workshop that introduced a framework to teach CR using an interactive, case-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…For example, in our study problem representation and illness scripts were identified as the most important concepts to teach in clinical clerkships. In a faculty development study, a single case-based, interactive workshop followed by role-play exercises resulted in significant improvement in faculty’s use of problem representation and illness scripts when teaching [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our study problem representation and illness scripts were identified as the most important concepts to teach in clinical clerkships. In a faculty development study, a single case-based, interactive workshop followed by role-play exercises resulted in significant improvement in faculty’s use of problem representation and illness scripts when teaching [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CR training sessions for the undergraduate healthcare profession were categorized into sessions to train and guide educators regarding the domains of CR education, 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 and sessions to guide educators in how to use a newly developed tool 28 , 29 or mobile application 30 to facilitate CR education. These sessions were conducted either as stand-alone sessions 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 or as an independent topic in a series of faculty development programs. 19 , 20 These training sessions had similar aims of guiding and training educators in CR to empower them in their teaching.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 20 These training sessions had similar aims of guiding and training educators in CR to empower them in their teaching. Specifically, these training sessions were aimed at providing guidance in the cognitive steps and CR framework 21 , 22 , 25 , 26 , 27 ; diagnostic error and bias 24 ; and identification of learners with CR difficulties. 23 , 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This group had expertise in assessment and feedback and development of clinical reasoning curricula across the educational continuum-undergraduate medical education, graduate medical education, and faculty development. [24][25][26] This panel iteratively reviewed the assessment and plans of randomly selected de-identified admission notes from the NYU Langone EHR written by internal medicine residents and medicine subspecialty fellows using the IDEA assessment tool core domains. To help ensure the selected notes were diagnostic in nature rather than more management related, pre-procedure notes and admission notes written after 3 days of the admitting date were excluded.…”
Section: Content Validationmentioning
confidence: 99%